2019
DOI: 10.1111/jocn.15037
|View full text |Cite
|
Sign up to set email alerts
|

Factors for self‐management activities among rural patients with chronic hepatitis B: A cross‐sectional study

Abstract: Aims and objectives To assess the self‐management activities among rural patients with chronic hepatitis B (CHB), and the influence of psychosocial and demographic factors on their self‐management activities. Background Chronic hepatitis B is a serious public health concern. Rural patients may have limited access to healthcare services. Although self‐management is important for controlling chronic hepatitis B, few studies focus on the self‐management activities among rural patients with chronic hepatitis B. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…It was confirmed that the demographic and clinical characteristics influence the self‐management of COPD in this study. Gender (women) had a significant direct effect on COPD self‐management, consistent with previous studies (Bringsvor et al, 2018; Kong et al, 2019). The level of self‐management might be higher in women, because women with chronic diseases tend to participate more positively and actively in life than men (Nolte et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was confirmed that the demographic and clinical characteristics influence the self‐management of COPD in this study. Gender (women) had a significant direct effect on COPD self‐management, consistent with previous studies (Bringsvor et al, 2018; Kong et al, 2019). The level of self‐management might be higher in women, because women with chronic diseases tend to participate more positively and actively in life than men (Nolte et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…In previous literature, demographic and clinical characteristics of patients with COPD are related to self-management. The level of self-management in women is higher than that in men (Bringsvor et al, 2018;Kong et al, 2019). Dyspnoea is one of the most frequent symptoms (Lim et al, 2017), and airflow limitation is a characteristic finding of COPD (Global initiative for chronic obstructive lung disease, 2021); Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage is an indicator of the severity of airflow limitation and has been used as a clinical indicator in many studies (Safka et al, 2017;Vogelmeier et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] In the forth part, Social Support Rating Scale, 3 dimensions of objective support, subjective support and the utilization of social support were evaluated with 10 items. [ 21 ] The last part was General Self-Efficacy Scale. [ 16 ] All scales have passed the test of reliability and validity, and have good reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that individuals at high risk for stroke with higher self-efficacy are more confident in dealing with various setbacks, thus gaining better self-management (Zhou, 2019), such as adherence to medicine, monitoring symptoms and keeping good communication with healthcare providers (Kong et al, 2019(Kong et al, , 2021. The positive relationship between self-efficacy and self-management has also been found in patients with stroke (Jones & Riazi, 2011), diabetes (Kong et al, 2019(Kong et al, , 2021Riegel et al, 2017), heart disease (Kong et al, 2019(Kong et al, , 2021Riegel et al, 2017) or kidney disease (Li et al, 2014). Furthermore, self-efficacy interventions have been proved to be successful in improving self-management behaviours among patients with diabetes (Ahmad Sharoni et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%